Water resources using hydro economic models for decisions in water, energy, food and environment (WEFE): Examples from Pakistan - Davies, Stephen; Akram, Iqra; Ali, Muhammad Tahir (International Food Policy Research Institute, 2024)
A presentation for the NEXUS Gains International Winter School 2024 entitled “Advancing Sustainable Development and Climate Resilience through Integrated Water-Energy-Food Ecosystem Solutions.” December 23 - 27, 2024 - Roomy Hotel, Islamabad, Pakistan.